An overview of the existing and future state of the art advancement of hybrid energy systems based on PV-solar and wind - Soudagar M.E.M.; Ramesh S.; Yunus Khan T.M.; Almakayeel N.; Ramesh R.; Nik Ghazali N.N.; Cuce E.; Shelare S. (Oxford University Press, 2025)
Increasing solar and wind power use in existing power systems could create significant technical issues, especially for grids with poor connectivity or stand-alone systems needing more adequate storage capacity. This is due to the unpredictable and intermittent nature of solar and wind power. The intermittent nature of solar and wind resources can be reduced by integrating them optimally, making the entire system more reliable and cost-effective to operate. The advantages and disadvantages of hybrid wind and solar energy integration systems are discussed in this research. The impact of voltage and frequency oscillations and harmonics is amplified in weak grids, affecting both grid-connected and stand-alone systems. This may be fixed by ensuring that hybrid systems are well designed, equipped with cutting-edge quick reaction control capabilities, and optimized. This review offers an overview of existing advances in PV-solar and wind-based hybrid energy systems while exploring potential future developments. Further, this review also provides an overview of the primary studies published on optimum design considerations for compactness, topologies for power electronics, and control. As the global energy environment shifts toward sustainability and resilience, this review helps researchers, policymakers, and industry stakeholders understand, adapt, and enhance PV-solar-wind hybrid energy systems. ? 2024 Oxford University Press. All rights reserved.